PENERAPAN BUDAYA KESELAMATAN DAN KESEHATAN KERJA DALAM PEMBERIAN ASUHAN KEPERAWATAN DI RSU SEMBIRING DELI TUA TAHUN 2023 - Sihotang, Tini Wulandari (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Work accidents are work-related events that result in injury or illness depending on the severity and can cause death. There are many job demands that are owned by nurses that allow work accidents to occur in hospitals. The type of research used is quantitative research using a cross-sectional approach with research that aims to analyze the application of a culture of occupational safety and health in providing nursing care at Sembiring Deli Tua Public Hospital in 2023. It will be held at Sembiring Deli Tua Hospital from November 2022 to June 2023. The sample size is calculated using the Slovin formula, from the calculations a minimum sample size of 78 people is obtained. The sampling technique used was consecutive sampling. The results showed that cooperation within the unit, supervisors supporting patient safety, communication, frequency, incident reporting, organizational learning were related to the provision of nursing care at Sembiring Deli Tua Hospital but the most dominant was organizational learning which had the opportunity 5,856 times to lead to good nursing care at the hospital. Sembiring Old Deli. It is hoped that the hospital will conduct outreach and training to health workers regarding the measures used in the hospital to ensure that all reports are made openly and a learning process occurs as well as implementing appropriate actions/solutions. Hospital management can review policies regarding nursing supervision and as a reference in an effort to improve patient safety culture which has an impact on improving hospital quality.